2016
DOI: 10.1038/onc.2016.14
|View full text |Cite
|
Sign up to set email alerts
|

HGF/Met and FOXM1 form a positive feedback loop and render pancreatic cancer cells resistance to Met inhibition and aggressive phenotypes

Abstract: PurposeHepatocyte growth factor (HGF)/Met signaling plays critical roles in pancreatic ductal adenocarcinoma (PDA) development and progression and is considered a potential therapeutic target for this disease. However, the mechanism of aberrant activation of HGF/Met signaling and resistance to Met inhibition in PDA remains unclear.Experimental DesignThe mechanistic role of cross-talk between Forkhead box M1 (FOXM1) and HGF/Met signaling in promotion of PDA growth and resistance to Met inhibition was examined u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 41 publications
0
36
0
Order By: Relevance
“…The latter has been repeatedly implicated in drug-resistant solid cancers; e.g., in retinoblastoma [ 35 ], bladder cancer [ 36 ] and colorectal cancer [ 37 ], in which the heightened drug-efflux activity could be functionally linked to FOXM1-dependent upregulation of ABCC4, ABCG2 and ABCC10, respectively. Also playing a role may be other pathways of drug resistance that operate in solid tumors [ 38 ]; e.g., inhibition of ubiquitination-dependent FOXM1 degradation via interacting proteins, such as OTUB1 (OTU deubiquitinase, ubiquitin aldehyde binding 1) [ 39 ]; crosstalk of FOXM1 with other cellular signal transduction pathways, such as HGF / Met (hepatocyte growth factor / Met proto-oncogene, receptor tyrosine kinase) [ 40 ] and AKT (AKT serine / threonine kinase 1) [ 41 ]; and metabolic changes that effect increased oxidative defense capacity, as seen in radio-resistant head and neck squamous cell carcinoma [ 42 ]. Targeting the interactions and pathways described above – perhaps in conjunction with targeting FOXM1 directly using established [ 43 ] or emerging [ 44 ] small-drug inhibitors – may afford the re-sensitization of relapsed FOXM1 High myeloma to Bz and other drugs that were effective at earlier stages of myeloma therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The latter has been repeatedly implicated in drug-resistant solid cancers; e.g., in retinoblastoma [ 35 ], bladder cancer [ 36 ] and colorectal cancer [ 37 ], in which the heightened drug-efflux activity could be functionally linked to FOXM1-dependent upregulation of ABCC4, ABCG2 and ABCC10, respectively. Also playing a role may be other pathways of drug resistance that operate in solid tumors [ 38 ]; e.g., inhibition of ubiquitination-dependent FOXM1 degradation via interacting proteins, such as OTUB1 (OTU deubiquitinase, ubiquitin aldehyde binding 1) [ 39 ]; crosstalk of FOXM1 with other cellular signal transduction pathways, such as HGF / Met (hepatocyte growth factor / Met proto-oncogene, receptor tyrosine kinase) [ 40 ] and AKT (AKT serine / threonine kinase 1) [ 41 ]; and metabolic changes that effect increased oxidative defense capacity, as seen in radio-resistant head and neck squamous cell carcinoma [ 42 ]. Targeting the interactions and pathways described above – perhaps in conjunction with targeting FOXM1 directly using established [ 43 ] or emerging [ 44 ] small-drug inhibitors – may afford the re-sensitization of relapsed FOXM1 High myeloma to Bz and other drugs that were effective at earlier stages of myeloma therapy.…”
Section: Discussionmentioning
confidence: 99%
“…(5,28) Our previous microarray data and various other studies indicated that both EGFR and MET can regulate FOXM1 expression. (6,(23)(24)(25)(26)(27) Here we report that TCPOBOP-driven FOXM1 induction and its downstream gene network activation was remarkably impaired in [MET KO + EGFRi] mice, which might contribute to attenuated proliferation in our model. Conversely, the inverse phenotype to our model (i.e., increased proliferation but reduced expression of drug metabolic enzymes) previously reported in β-catenin KO mice following TCPOBOP treatment was attributed to increased FOXM1 levels.…”
Section: Discussionmentioning
confidence: 76%
“…Our previous data and several other reports indicated that both MET and EGFR can regulate an important transcription factor, FOXM1, which governs transcription of genes important for DNA replication and mitosis. (6,(23)(24)(25)(26)(27) FOXM1 is considered to be critical for inducing TCPOBOP-mediated hepatocyte proliferation. (3,5,14,16,22,28) Consistent with these previous reports, FOXM1 was remarkably induced by TCPOBOP at all of the time points in control mice with peak induction (10-fold) coinciding with the time point of peak proliferation (day 2) ( Fig.…”
Section: Downregulation Of Foxm1 Transcription Factor and Its Downstrmentioning
confidence: 99%
“…Because of previous reports that elevated expression of the tyrosine kinase proto‐oncogene MET is a marker of tumor aggressiveness in bladder cancer and has been proposed as both a biomarker and a therapeutic target, we investigated MET expression in the canine bladder mRNA‐seq dataset. We found that MET is 4.6‐fold upregulated in canine bladder cancer versus normal bladder samples ( P < .05, Welch's t‐ test on log 2 ‐transformed, sample‐normalized data; see Methods) (Supporting Information Fig.…”
Section: Resultsmentioning
confidence: 99%